Synthetic Biomimetic Polymethacrylates: Promising Platform for the Design of Anti-Cyanobacterial and Anti-Algal Agents - Mikula, Přemysl; Mlnaříková, Marie; Nadres, Enrico T; Takahashi, Haruko; Babica, Pavel; Kuroda, Kenichi; Bláha, Luděk; Sovadinová, Iva (Polymers, 2021)
Extensive, uncontrolled growth of algae and cyanobacteria is an environmental, public health, economic, and technical issue in managing natural and engineered water systems. Synthetic biomimetic polymers have been almost exclusively considered antimicrobial alternatives to conventional antibiotics to treat human bacterial infections. Very little is known about their applicability in an aquatic environment. Here, we introduce synthetic biomimetic polymethacrylates (SBPs) as a cost-effective and chemically facile, flexible platform for designing a new type of agent suitable for controlling and mitigating photosynthetic microorganisms. Since SBPs are cationic and membranolytic in heterotrophic bacteria, we hypothesized they could also interact with negatively charged cyanobacterial or algal cell walls and membranes. We demonstrated that SBPs inhibited the growth of aquatic photosynthetic organisms of concern, i.e., cyanobacteria (Microcystis aeruginosa and Synechococcus elongatus) and green algae (Chlamydomonas reinhardtii and Desmodesmus quadricauda), with 50% effective growth-inhibiting concentrations ranging between 95 nM and 6.5 μM. Additionally, SBPs exhibited algicidal effects on C. reinhardtii and cyanocidal effects on picocyanobacterium S. elongatus and microcystin-producing cyanobacterium M. aeruginosa. SBP copolymers, particularly those with moderate hydrophobic content, induced more potent cyanostatic and cyanocidal effects than homopolymers. Thus, biomimetic polymers are a promising platform for the design of anti-cyanobacterial and anti-algal agents for water treatment.
Keywords: algae; polymethacrylates; antimicrobials; biomimetic polymers; water treatment; cyanobacteria